2022
DOI: 10.1002/er.7987
|View full text |Cite
|
Sign up to set email alerts
|

The kinetic and experimental study for the syngas production from ethanol dry reforming over a Ni‐Cu / La 2 O 3 catalyst

Abstract: Summary The mechanistic kinetic model through Langmuir‐Hinshelwood (LH) isotherm was derived for ethanol dry reforming (EDR) processaccompanied by the ethanol decomposition (ED) and methane dry reforming (MDR). For justifying mechanistic relation, EDR tests wereaccomplished under a vast range of operating variables (including temperature varied from 500°C to 900°C and ratio of CO2 to C2H5OH in the inlet feed [C/E ratio] of 1‐3) over a Ni‐Cu/La2O3 catalyst. The physicochemical properties of the fresh and spent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…18 In the present study acetaldehyde was not observed while it is often observed or stated in the literature. 1–26 After hydrogen is eliminated from structure (B), successive rapid reactions including structures (C), (D), (E) and (A) in order could occur. In the structure (C), methyl, carbonyl and hydride groups are formed on the surface through C–C bond scission and C–H bond scission of adsorbed acetaldehyde on Cu I species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…18 In the present study acetaldehyde was not observed while it is often observed or stated in the literature. 1–26 After hydrogen is eliminated from structure (B), successive rapid reactions including structures (C), (D), (E) and (A) in order could occur. In the structure (C), methyl, carbonyl and hydride groups are formed on the surface through C–C bond scission and C–H bond scission of adsorbed acetaldehyde on Cu I species.…”
Section: Resultsmentioning
confidence: 99%
“…Dry reforming using greenhouse gas CO 2 to produce hydrogen and synthesis gas could be an ideal process if carbon neutral biomass was combined. 1–26 Although dry reforming of methane, one of the fossil fuels, has already been developed extensively, 27–37 the continuous utilization of fossil fuels might increase CO 2 even if methane fermentation could be utilized. Instead of the use of methane, dry reforming of ethanol (DRE) 1–26 would be one of the promising attempts to achieve a complete carbon neutral system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations